A study on the diagnosis of minimal endoscopic lesions in nonerosive reflux esophagitis using computed virtual chromoendoscopy (FICE) - Gomes Jr.,Claudio Antonio Rufino (2011)
CONTEXT: Gastroesophageal reflux disease is very prevalent in the world. Endoscopically it can be classified as nonerosive when there is no mucosal erosive lesion on endoscopy. The presence of endoscopic minimal lesions is included in the Los Angeles classification for reflux disease. Virtual chromoendoscopy Fuji Intelligent Color Enhancement (FICE) is an endoscopic technique that enhances detection of small lesions of the digestive tract. OBJECTIVE: To evaluate whether the use of FICE improves the diagnosis of minimal lesions on endoscopy, and to assess the association of symptoms with minimal lesions in patients with nonerosive reflux disease. METHODS: One hundred fifty-five patients were enrolled, 62 with typical reflux symptoms and 93 without esophageal symptoms. The patients had normal esophageal endoscopy or minimal lesions. Each patient was examined initially by conventional video endoscopy and then using FICE. RESULTS: Among 155 patients, 113 had a normal conventional endoscopy and 42 had minimal lesions. Sixty-two patients had typical reflux symptoms, and 93 other symptoms unrelated to reflux. In 104 patients, the esophageal mucosa was normal for both conventional endoscopy and FICE, in 42 patients both techniques showed minimal lesions, in 9 patients conventional endoscopy was normal and minimal lesions were shown by FICE. The height and circumference of minimal lesions were greater using FICE than that measured by conventional endoscopy. There was a significant association of the presence of minimal lesions with male gender, but not with alcoholism, smoking, anti-inflammatory drugs and age. The diagnosis of minimal lesions was observer-dependent, both in conventional endoscopy as using FICE. CONCLUSIONS: The use of FICE improves the diagnosis of minimal lesions as compared to conventional videoendoscopy, although this diagnosis remains observer-dependent. There was no association between the presences of minimal lesions with reflux symptoms.